Identifying factors affecting the creation of social interactions and functional security (case study: Mehr housing in Boroujard city) - Seyed Mohammad Ali Ahmadi Tabatabaie; Ferial Ahmadi; Vahid Heidar Nattaj (مسکن و محیط روستا)
by growth of population and the increasing need for housing, the establishment and design of Mehr housing complexes around cities began. However, due to reasons such as inappropriate location selection, the residence of individuals with different cultures, and the lack of a coherent plan, the quality does not meet the desired standards like a traditional Iranian house. Neglecting the quality of housing leads to a decrease in security and social interactions in residential complexes. This research aims to identify the factors influencing the creation of social interactions and functional security, as well as the mutual impact of these two aspects on each other in Mehr housing in Borujerd city. The research method is descriptive-analytical within a survey and case study framework, utilizing interpretive and survey methods in the research process to examine the causes of lack of security and social interaction in the case study sample. Sample size of 373 individuals was calculated and for data analysis, SPSS26 software was used along with standard deviation test, Friedman ranking, and Spearman correlation. The findings of this research confirm a direct correlation between security and social interaction overall with a coefficient of 0.514. The correlation between the dimensions of security and social interaction in physical, functional, and perceptual aspects is confirmed with coefficients of 0.613, 0.295, and 0.159, respectively. Additionally, the correlation between the criteria and influential factors on security and social interaction is confirmed in all cases except for public participation and social cohesion, which have inverse relationships. Functional factors have the most significant impact on creating social interaction, while perceptual factors have the most significant impact on creating security. Furthermore, the overall correlation between security and social interaction, as well as their different dimensions, is confirmed. However, the relationship between the influential factors on different dimensions of security and social interaction is not confirmed. In the case study sample, due to physical weakness and improper design, all components are either ineffective or contribute to decreasing security and social interaction.